Fuzzy Logic Transformer Design Algorithm (FLTDA) - R. R. Mudholkar; S. R. Sawant; G. G. Tengshe; A. B. Bagwan (Active and Passive Electronic Components)
In the present communication we report a novel fuzzy based algorithm developed for transformer designing. The Fuzzy Logic Transformer Design Algorithm (FLTDA) incorporates the experience of human transformer designers and builders in terms of minimum of fuzzy rules. It easily accomodates the linguistic design concepts and linguistic values of transformer specifications. The FLTDA allows to use assumptions, approximations, estimations and guess-figures for specifications in the beginning of design-route and adjusts the parameters in iterations yielding optimum design results.